Novel fenofibrate derivatives as cannabinoid receptor ligands - Spencer, Sarah Jane (2011)
Fenofibrate is a PPARα agonist, used to treat dyslipidemia. Unpublished work that has been previously carried out in our group has identified that fenofibrate also displays affinity for the cannabinoid receptors, CB1 and CB2. A dual receptor ligand, with the PPARα agonist activity of fenofibrate, combined with antagonist activity at the CB1 receptor, or agonist activity at the CB2 receptor, could reduce appetite, decrease plasma triglyceride levels, increase high density lipoprotein (HDL) levels, lower low density lipoprotein (LDL) levels and reduce atherosclerosis. This could enable the multi-symptomatic treatment of obesity with the advantage of avoiding side effects associated with taking multiple medications. However, whilst fenofibrate has affinity for the cannabinoid receptors, only its active metabolite; fenofibric acid (10b) activates PPARα. This project sought to develop novel ligands for the cannabinoid receptors that retain activity at PPARα. A series of amide derivatives of fenofibrate were synthesised, and pharmacological testing revealed that the piperidinyl (48g) and morpholino (48h) derivatives had agonist activity and a higher affinity for the cannabinoid receptors than fenofibrate. However these derivatives failed to bind and activate PPARα. Although a dual PPARα / cannabinoid receptor ligand has not been found with these amide derivatives, the compounds synthesised could provide a platform for the further development of cannabinoid receptor ligands of this novel class. This was demonstrated by further modifications to compounds (48g) and (48h) which indicated that activity at the cannabinoid receptors is tuneable.